2010
DOI: 10.1074/jbc.m110.143008
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cytoplasmic Adaptor for Retinoic Acid Receptor (RAR) and Thyroid Receptor Functions as a Derepressor of RAR in the Absence of Retinoic Acid*

Abstract: In most mammalian cells, the retinoic acid receptor (RAR) is nuclear rather than cytoplasmic, regardless of its cognate ligand, retinoic acid (RA). In testis Sertoli cells, however, RAR is retained in the cytoplasm and moves to the nucleus only when RA is supplied. This led us to identify a protein that regulates the translocation of RAR. From yeast two-hybrid screening, we identified a novel RAR-interacting protein called CART1 (cytoplasmic adaptor for RAR and TR). Systematic interaction assays using deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Different from most mammalian cells, where RA receptors (RARs) are nuclear regardless of their cognate ligands, in Sertoli cells RARs move from the cytoplasm to the nucleus only when RA is bound (42). Thus, to establish the in vivo response of Sertoli cells to RA, the number of Sertoli cells with nuclear expression of the RARa was counted, comparing the number of RARaþ Sertoli cells in SCOS tubules of SRpos and SRneg iNOA men to that in the seminiferous tubules still containing germ cells.…”
Section: Figurementioning
confidence: 99%
“…Different from most mammalian cells, where RA receptors (RARs) are nuclear regardless of their cognate ligands, in Sertoli cells RARs move from the cytoplasm to the nucleus only when RA is bound (42). Thus, to establish the in vivo response of Sertoli cells to RA, the number of Sertoli cells with nuclear expression of the RARa was counted, comparing the number of RARaþ Sertoli cells in SCOS tubules of SRpos and SRneg iNOA men to that in the seminiferous tubules still containing germ cells.…”
Section: Figurementioning
confidence: 99%
“…Other studies demonstrated that, in Sertoli cells, RAR ␣ is a substrate for small ubiquitin-like modifi er-2 (SUMO-2) and that a dynamic process of sumoylation and desumoylation infl uences the cytosolic/nuclear localization of the receptor ( 153 ). In Sertoli cells and hepatic stellate cells, a cytosolic localization of RAR ␣ has been also observed upon interaction with the cytoplasmic adaptor for RAR and TR (CART1) protein or with cytoskeleton proteins that sequester the receptor out of nuclei ( 154,155 ). Given that sumoylation and protein interactions can be regulated by phosphorylation processes, one cannot exclude that a dynamic process of phosphorylation, sumoylation, and protein interaction infl uences the cytosolic/nuclear localization of RARs.…”
Section: Unconventional Picture In Ra Signaling: Cytosolic Localizatimentioning
confidence: 99%
“…RA induces the expression of the thyroid hormone transporter and monocarboxylate transporter, which demonstrates cross-talk between RA signaling and thyroid hormone signaling in early development at the level of the thyroid hormone transporter ( 28 ). Although RAR and thyroid receptors do not seem to interact directly physically, they share some cofactors so that some form of competition may occur between the two ligands and their receptors ( 29 ). In conclusion, there are many levels at which vitamin A can interact with the physiology of the hypothalamo-pituitary-thyroid axis, which was also reflected by our findings, as significant positive correlations were detected with T3, FT3 and TSH, and negative correlations were detected with FT4.…”
Section: Discussionmentioning
confidence: 99%